THE EARLY SCHOOLS OF FIQH AND EXCESSIVE COMMENT PROBLEM - Arslan, Giyasettin (Ilahiyat Bilimleri Arastirma Vakfi, 2005)
The jurisprudence reading (fiqh) is one of the most important readings through the reading of the Quran. Although this reading was a correct way at the early period but later it turned in to excessive interpretation. You will experience striking examples of this excessive interpretations in this article.
Keywords: Jurisprudence reading; Islamic law; Excessive interpretation